Linking Leadership Style, Work Culture, and Motivation to Employee Performance: A Study of the Jayapura City Regional Secretariat - Kumendong, Nansy Maria M.; Kambuaya, Balthasar; Wambrauw, Oscar O. (Magister Manajemen Universitas Cenderawasih, 2025)
This study aims to analyze the influence of transformational leadership style, work culture, and work motivation on employee performance at the Regional Secretariat of Jayapura City, both partially and simultaneously. The research employed a quantitative approach with a correlational design. The population comprised all civil servants at the Regional Secretariat of Jayapura City, with a sample of 63 respondents selected through purposive sampling. Data were collected using a questionnaire and analyzed through multiple linear regression. The results indicate that transformational leadership style, work culture, and work motivation have a positive and significant effect on employee performance, both individually and jointly.